2021
DOI: 10.1017/s1463423621000426
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of diagnosed specific back pain in primary health care in Region Västra Götaland: a register study of 1.7 million inhabitants

Abstract: Objectives: To evaluate the one-year prevalence of diagnosed specific back pain in Region Västra Götaland, inhabiting 1.7 million people. Designs: A retrospective register study. Settings: Data from 2014 to 2019 were extracted from the VEGA register, which holds all health data from all publicly funded health care establishments in Region Västra Götaland. Aggregated data are presented as the one-year prevalence of unique individuals diagnosed with International Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Excessive BV causes biomechanical disorders such as back pain, avoidance of physical activity, and biopsychological problems such as cosmetic dissatisfaction [4,14,15]. In the present study, we showed a relationship between TBV and TKA, which may be associated with the development of back pain.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Excessive BV causes biomechanical disorders such as back pain, avoidance of physical activity, and biopsychological problems such as cosmetic dissatisfaction [4,14,15]. In the present study, we showed a relationship between TBV and TKA, which may be associated with the development of back pain.…”
Section: Discussionsupporting
confidence: 55%
“…The increased load due to the large BV in the front side of the body can shift the body's center of gravity in the same direction [14,16,17]. Fındıkçıoğlu et al, showed that women with large breasts according to cup sizes had significantly greater TKA (measured by lateral radiography) than women with small breasts [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnosis studied, the age distribution is not expected to be the same for diagnoses such as lumbar spine stenosis; for example, lumbar root canal stenosis heavily depends on degeneration of the spine, which increases with age [ 18 ]. If confounding factors significantly influenced our diagnostic groups that retrieved a large amount of opioids, we expect to see the same pattern as we see in the total population; however, we did not see this pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The primary and secondary endpoints have been used in large national or international studies and tested for validity and reliability [ 42 , 44 ]. Moreover, register data will be collected retrospectively from the National Board of Health and Welfare: each registered holder, health care encounters from the regional patient register VEGA [ 45 ], use of prescribed drugs dispensed in outpatient pharmacies from the Swedish Prescribed Drug Register (SPDR) [ 46 ], use of home help services and supported living facilities, municipal health care use, and information about potential causes of death.…”
Section: Methods and Designmentioning
confidence: 99%